Triple interactions for induced systemic resistance in plants - Jung, Jihye; Ahn, Seongho; Kim, Do-Hyun; Riu, Myoungjoo (Frontiers in Plant Science, 2024)
Induced systemic resistance (ISR) is a crucial concept in modern agriculture, explaining plant defense mechanisms primed by rhizosphere stimuli and activated by subsequent infections.Biological factors contributing to ISR generally include plant growth-promoting microbes (PGPM). Bacillus spp., Pseudomonas spp., and Trichoderma spp. have been extensively studied for their plant growth-promoting characteristics and ISR effect against above-ground pathogens and insect infestations. These phenomena elucidate the bottom-up effects of how beneficial rhizosphere microbes help plants resist above-ground attacks. Conversely, soil microbiome analysis in the rhizosphere of plants infected by above-ground pathogens has shown increased beneficial microbes in the soil, a phenomenon termed 'soil legacy effects'. This represents the top-down effects of above-ground attackers on plants' rhizosphere environments. Interestingly, recent studies have shown that above-ground stimuli not only recruit PGPM in the rhizosphere but also that these PGPM influence plant defense responses against subsequent pathogen infections. This can be seen as a four-step plant defense mechanism involving above-ground attackers, host plants, rhizosphere microbes, and subsequent attacks. This represents an active defense mechanism that overcomes the limitations of sessile plants. This review summarizes plant ISR mechanisms in terms of triple inter-organism interactions and provides molecular evidence for each step.